PERAN BRAND IMAGE MEMEDIASI PENGARUH SOCIAL MEDIA MARKETING TERHADAP PURCHASE INTENTION (Studi Pada Kedai Berbagi Kopi Peguyangan Denpasar) - Sastrawan, Kadek Adi; Pramudana, Komang Agus Satria (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
The large amount of coffee production in Indonesia is certainly a business opportunity by processing coffee products into coffee-based drinks. Supported by abundant raw materials and a large market, Indonesia holds great potential for the development of its coffee processing industry. This creates an excellent opportunity for entrepreneurs to venture into the coffee processing business. This research was conducted at the Kedai Berbagi Kopi, North Denpasar. The aim of this research is to explain the influence of brand image mediating the influence of social media marketing on purchase intention. This research uses Consumer Behaviour as a theoretical basis with a sample size of 100 people and uses purposive sampling techniques. The data collection was conducted through interviews, observation, and questionnaires. The analysis methods used include Classic Assumption Test, Path Analysis, and VAF TestTop of FormBottom of Form. Based on the analysis results, it was found that social media marketing has a positive and significant influence on purchase intention, social media marketing has a positive and significant influence on brand image, brand image has a positive and significant influence on purchase intention, and brand image can partially mediate the influence of social media marketing on purchase intention. The implications of these results can be utilized by Kedai Berbagi Kopi Peguyangan in developing appropriate strategies according to consumer behavior patterns.